The implementation of curricular strategies in career Degree in Primary Education - Moré Estupiñán, Mavel (Avances en Supervisión Educativa, 2017)
In Cuba, the integral formation of university graduates is a necessity. In this endeavor, the Curricular Strategies acquire singular importance. This study/research reveals the strengths and weaknesses in the implementation of the Curricular Strategies in career Degree in Elementary Education. Correspondingly, the objective is: to propose a system of procedures for perfecting the implementation of Curricular Strategies in the direction in the management of the educational of the different disciplines of this career. The implementation of this system of procedures in different subjects of the career already exhibits satisfactory results.